Superoxide Dismutase Prevents SARS-CoV-2-Induced Plasma Cell Apoptosis and Stabilizes Specific Antibody Induction. (17th January 2022) - Mo, Li-Hua; Luo, Xiang-Qian; Ma, Ke; Shao, Jian-Bo; Zhang, Guo-Hao; Liu, Zhi-Gang; Liu, Da-Bo; Zhang, Huan-Ping; Yang, Ping-Chang
Abstract : The infection of coronavirus disease (COVID-19) seriously threatens human life. It is urgent to generate effective and safe specific antibodies (Abs) against the pathogenic elements of COVID-19. Mice were immunized with SARS-CoV-2 spike protein antigens: S ectodomain-1 (CoV, in short) mixed in Alum adjuvant for 2 times and boosted with CoV weekly for 6 times. A portion of mice were treated with Maotai liquor (MTL, in short) or/and heat stress (HS) together with CoV boosting. We observed that the anti-CoV Ab was successfully induced in mice that received the CoV/Alum immunization for 2 times. However, upon boosting with CoV, the CoV Ab production diminished progressively; spleen CoV Ab-producing plasma cell counts reduced, in which substantial CoV-specific Ab-producing plasma cells (sPC) were apoptotic. Apparent oxidative stress signs were observed in sPCs; the results were reproduced by exposing sPCs to CoV in the culture. The presence of MTL or/and HS prevented the CoV-induced oxidative stress in sPCs and promoted and stabilized the CoV Ab production in mice in re-exposure to CoV. In summary, CoV/Alum immunization can successfully induce CoV Ab production in mice that declines upon reexposure to CoV. Concurrent administration of MTL/HS stabilizes and promotes the CoV Ab production in mice.